Identification of novel salivary candidate protein biomarkers for tuberculosis diagnosis: A preliminary biomarker discovery study. (September 2021) - Mutavhatsindi, Hygon; Calder, Bridget; McAnda, Shirley; Malherbe, Stephanus T.; Stanley, Kim; Kidd, Martin; Walzl, Gerhard; Chegou, Novel N.
Abstract: Background: There is an urgent need for new, accurate, rapid, and affordable tuberculosis (TB) diagnostic tests. The aim of the present study was to use mass spectrometry to identify new preliminary candidate TB diagnostic protein biomarkers in saliva obtained from individuals with TB, and patients with other respiratory diseases (ORD). Methods: Saliva samples were collected from 22 individuals who self-presented with symptoms suggestive of TB as part of a larger TB biomarker project. Purified salivary proteins were subjected to tryptic digestion peptides were analyzed using a QExactive Orbitrap Mass Spectrometer. Data are available via ProteomeXchange with identifier PXD027294. Identified proteins were subjected to gene ontology and ingenuity pathway analysis for functional enrichment analysis. Results: 26 of the 652 identified proteins significantly discriminated individuals with TB from those with ORD after Benjamini Hochberg correction (5% FDR), with five of these proteins diagnosing TB with an AUC ≥ 0.80. A 5-protein biosignature comprising of P01011, Q8NCW5, P28072, A0A2Q2TTZ9, and Q99574 diagnosed TB with an AUC of 1.00 (95% CI, 1.00–1.00), sensitivity of 100% (95% CI, 76.2–100%) and specificity of 90.9% (95% CI, 58.7–99.8%) after leave-one-out cross validation. Conclusions: We identified novel candidate salivary protein biomarkers and biosignatures with strong potential as TB diagnostic candidates. Our results are preliminary and require validation in larger studies.